Demitizzare Cesare Pavese. Studio su colpa e destino (ENTHYMEMA, 2020)
This essay investigates myth in Cesare Pavese’s narrative works from a Ricœurian perspective. It focuses on passages where the first-person narrator, at the tragic climax of the scene, introduces a sense of guilt. The importance of guilt to Pavese’s thought has often been given a biographical rationale, but this essay reexamines it in the light of a specific theory of myth. The steps in this reexamination are 1) tackling the problem of de-mythization, which is central to Pavese’s theoretical writings; 2) highlighting the link between guilt and a conception of time, including in narratological terms; and 3) showing how guilt does not arise from the author’s life but from his reflection on time, on the problem of evil, and on the finitude of human life.
Keywords: Cesare Pavese; anthropology; hermeneutics; sense of guilt; psychoanalysis